ISLAMIC ECONOMIC LAW "A CONTINUOUS ECONOMIC STUDY PERSPECTIVE OF ISLAMIC ECONOMIC LAW" - Hadiat; Hasan Ridwan, Ahmad; Suntana, Ija; Rumatiga, Hidayat (DE'RECHTSSTAAT, 2024)
ausing a consumptive and materialistic nature which results in environmental damage due to uncontrolled use of resources. This research aims to determine sustainable economics from the perspective of Islamic Economic Law. This article uses a descriptive qualitative method with a normative-empirical approach. This research finds strong arguments and signs that Islamic economics is very concerned with sustainable economics with a focus on optimizing resources without ignoring environmental aspects, so that economic buildings are able to provide sustainable benefits. The real form of a sustainable Islamic economic system is at least visible in sharia banking's concern for the environment.